Radiation-Induced Morphea of the Breast in a Patient with Pre-Existing Mycosis Fungoides: A Diagnostic Challenge - Tala Mobayed; Toufic Eid; Ossama Abbas; Hiba Moukadem; Nagi El Saghir; Zeina Ayoub (Current Oncology, 2026)
Radiation-induced morphea (RIM) is a rare, immune-mediated late complication of breast radiotherapy that may clinically mimic radiation fibrosis, malignancy, or other inflammatory dermatoses. Diagnosis is particularly challenging in patients with pre-existing cutaneous T-cell lymphoma (CTCL), in whom new post-radiation skin lesions may raise concern for lymphoma involvement or progression. To the best of our knowledge, based on a non-systematic search of the available literature, this is the first reported case of radiation-induced morphea occurring in a patient with pre-existing mycosis fungoides (MF). A 55-year-old woman with a history of MF and right breast invasive lobular carcinoma underwent bilateral mastectomy followed by adjuvant chest wall radiotherapy. Approximately 6.5 years later, she developed a progressive erythematous, indurated plaque within the irradiated field. Given her history of MF, cutaneous lymphoma involvement and radiation-associated sarcoma were important diagnostic considerations. Punch biopsy demonstrated dermal collagen homogenization with a mixed inflammatory infiltrate, while immunohistochemistry showed preserved pan-T-cell antigen expression without an aberrant phenotype, supporting RIM rather than lymphoma. The patient was treated with topical corticosteroids followed by methotrexate, with mild-to-moderate improvement in erythema without complete resolution; subsequent reconstructive revision was followed by further improvement in erythema, breast softness, and cosmesis. This case highlights the diagnostic overlap between RIM and CTCL and underscores the importance of prompt biopsy and careful clinicopathological correlation in evaluating persistent or atypical post-radiation skin changes.